STRUCTURAL CHARACTERIZATION, PRODUCTION AND REPRODUCTIVE PHENOLOGY OF Mauritia flexuosa L.f. “aguaje” IN FOREST PLANTATIONS OF JENARO HERRERA, LORETO, PER - FREITAS ALVARADO, Luis (2023)
In this study, we generated information on the structural characteristics and reproductive phenology of aguaje in six plantations from 11,6 to 17 years old established in the Jenaro Herrera Research Centre, Loreto, Peru. We observed and measured plant survival, structural characteristics, and phenology. The results showed that plant survival ranged from 66% to 96%. The majority of the variables did not show an increase with the age of the plantation, except for the mean stem height and total height, which were higher in the 17‑year‑old plantation than in the younger plantations. The reproductive stage of plants began at 6‑7 years with the flowering of a few individuals and showing an increase in the number of flowering plants in the plantations each year. The flowering and fruiting of aguaje plants occurred annually with synchrony in the flowering of male and female plants. However, some plants did not flower for periods of one to three years. The flowering period lasted on average 58,2 ± 0,9 days in the female plants and 55,1 ± 0,8 days in the male plants, while fruiting lasted 275,0 ± 1,6 days. The obtained information contributes to the silvicultural knowledge for the management of aguaje in plantations.